Pengaruh Kemampuan Profesional Guru dan Pelatihan Terhadap Kinerja Guru - Hartati, Meri (Journal of Innovation in Teaching and Instructional Media, 2025)
This systematic literature review examines the influence of professional competence and training on teacher performance. To gain a deeper understanding of the complex relationship between training, professional competence, and teacher performance, this study integrates the findings of recent research. By employing the PRISMA protocol, ten peer-reviewed articles published between 2019 and 2024 were comprehensively evaluated from various online databases. The results indicate that teacher performance is influenced by both training and professional competence. This research contributes to the theory and practice of training and professional competence by providing insights into how to improve teacher performance through training. Additionally, this study thoroughly analyzes mediating and moderating factors that contribute to the success of training in enhancing teachers' professional capabilities.